If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2kx * 2kx = 0 Reorder the terms for easier multiplication: 2 * 2kx * kx = 0 Multiply 2 * 2 4kx * kx = 0 Multiply kx * kx 4k2x2 = 0 Solving 4k2x2 = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Divide each side by '4'. k2x2 = 0 Simplifying k2x2 = 0 The solution to this equation could not be determined.
| (3x+9)+(6x+7)= | | 5x+10=4x+15 | | 6x+10y+11=0 | | x^2+2kx-7=0 | | -10p+3(8+8n)=-6(n-4) | | 137-5x=-58-8x | | 5x+9=39-7x | | 3y(5y+9)=0 | | 63-6x=9+18 | | 5x-3(x-10)=100-2(3x+5) | | 2(g+6)=24 | | .83=-.4b+.33b | | 5(g+6)=24 | | 3(x^2+4x+4)=0 | | n+8m=d | | 30n=-5 | | x=42*7 | | 2x(x-1)=5(x+3) | | 2x^3-11x^2+22x-15=0 | | 5x+31=14x-92 | | 945000+x=10x | | X^3-2x^2+3x+4=0 | | 5x-3(x-2)=30-3(x+3) | | 0.2x^2-80x+2500=0 | | 2t=34 | | 19x-17=3(4x-13) | | E+5=25 | | 6x-11y=0 | | 0=(12x^2)+6x-18 | | 7x+2y=-15 | | t-11+3= | | 24d+12x+8d-12x= |